Opportunities and Risks of Developing a Green Economy - M. E. Kuznetsov (Мир новой экономики)
The relevance of the topic is due, firstly, to the importance of sustainable development as a priority task of the world community, and secondly, the green economy is an important tool for achieving it. The purpose of this research article is to identify the opportunities and risks of developing a green economy within the framework of sustainable development. Methods: the study was carried out using up-to-date data and sources, as well as a theoretical analysis of the basic principles and methodological approaches to the green economy. Scientific novelty: Summarizing the modern conceptual developments of the paradigm of the green economy, the author’s definition of this scientific category is proposed, which contributes to a more accurate understanding of the concept of the green economy. The main features and principles of the green economy are given. The results of the study: The article substantiates the directions of development of modern forms of green economy, taking into account which priority instruments of green financing are identified. The author analyzes the total volume of green financing in the world and provides a rating of countries according to the GGEI index. The article systematizes the opportunities and risks of developing a green economy. Practical significance: results and conclusions of the article can be useful both for the scientific community and for decision-makers at the level of States and international organizations that strive for sustainable development and environmental protection.